2007
DOI: 10.1108/17410390710717138
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing in Asian public administration sector: the case of Hong Kong

Abstract: PurposeThe paper seeks to investigate how culture, attitudes and barriers affect knowledge sharing in a Hong Kong government department.Design/methodology/approachInterviews and survey instruments were used to collect data for qualitative analysis.FindingsKnowledge management and knowledge sharing were welcome ideas in the Hong Kong government department. Informal and tacit knowledge sharing took place but the Chinese culture remained as a barrier to knowledge sharing.Research limitations/implicationsAs this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 16 publications
8
100
0
5
Order By: Relevance
“…Superiors play a major role to sustain learning activities, invoke change, training programs and knowledge management initiatives (Schraeder, tears, & Jordan, 2005;Rahman et al, 2013;Greiling & Halachmi, 2013;Yao et al, 2007;. Hence, the question is not whether or not support needs to be provided, but what kind of support is required.…”
Section: Culture In Open E-learning Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Superiors play a major role to sustain learning activities, invoke change, training programs and knowledge management initiatives (Schraeder, tears, & Jordan, 2005;Rahman et al, 2013;Greiling & Halachmi, 2013;Yao et al, 2007;. Hence, the question is not whether or not support needs to be provided, but what kind of support is required.…”
Section: Culture In Open E-learning Systemsmentioning
confidence: 99%
“…This stands for the perceived appropriateness of innovating routines, and of discussing problems and errors among peers. Knowledge and information are often conceived as power in the public sector and, thus, are not shared Yao, Kam, & Chan, 2007). Making an error is seen as a failure as opposed to a chance for improvement .…”
Section: Culture In Open E-learning Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, for reasons of public interests, a bulk of knowledge became widely accessible (Yao et al, 2007;Zhou, 2004) and many governments have worked to increase openness and transparency in their actions (Bertot, et al, 2010;Yao et al, 2007;Zhou, 2004). One of the motivations to do that is the increased demands for transparency for stimulus funds (Lamont, 2009) and the use of them, detection of anti-competitive behaviors and the growing demands for accountability (Kleinschmidt, 2009).…”
Section: Sharing Strategies and Transparency As An Organizational Excmentioning
confidence: 99%
“…Moreover, it is reported that there is a significant gap in the understanding and maturity of KM between Asian developing companies and those in developed countries. This can be explained by the fact that American and European companies have had KM strategies and initiatives in place for over a decade, while Asian developing companies are still attempting to understand and apply the concept of KM (Yao et al 2007).…”
Section: Related Researchmentioning
confidence: 99%